2014
DOI: 10.5392/jkca.2014.14.12.973
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Financial Determinants of Profitability for Korean Chaebol Firms by applying Conditional Quantile Regression (CQR) Model

Abstract: This study investigated one of the contemporary issues in the Korean capital market and two hypotheses of concern were tested on the financial determinants of profitability for the firms belonging to the Korean chaebols during the era of the post-global financial turmoil. The first hypothesis applying conditional quantile regression (CQR) estimation provided the evidence that leverage ratio, fixed asset utilization, and foreign ownership among the nine quantitative explanatory variables, had overall statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The findings are in support of the conventional rationale theorized in economics and finance: A firm may increase its value by hosting more cash inflow from foreign investors who have generally fewer financial constraints to access the credit market in the capital markets. Kim (2014) presented an empirical result that there was a positively significant effect of a proportion of foreign ownership on a firm's profitability. Specifically, higher profitability was likely to arise from superior management skills inclusive of utilization of asymmetric information which foreign (institutional) investor may possess.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The findings are in support of the conventional rationale theorized in economics and finance: A firm may increase its value by hosting more cash inflow from foreign investors who have generally fewer financial constraints to access the credit market in the capital markets. Kim (2014) presented an empirical result that there was a positively significant effect of a proportion of foreign ownership on a firm's profitability. Specifically, higher profitability was likely to arise from superior management skills inclusive of utilization of asymmetric information which foreign (institutional) investor may possess.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Kim and Yang (2014) analysed the determinants of FDI inflows to Korea over the period from 1995 to 2012 using the panel quantile regression model. They found that GDP, employment and human resource education levels of the host country were significant determinants of FDI inflows only when the level of the inflow was low.…”
Section: Systematic Literature Review (Slr) Methodologymentioning
confidence: 99%